Jesus, the Gospels, and the Galilean crisis - Ferda, Tucker S. (London Bloomsbury Publishing PLC, 2018)
Cover -- Contents -- List of Figures -- Preface -- Chapter 1 -- Introducing the Galilean Crisis -- 1. Aims -- 2. Problems Stated -- 3. Approach -- 4. The Historical Jesus and Method -- Chapter 2 -- Interpretive Precursors and Habits of Reading -- 1. Theological Starting Points and Developments -- 2. Harmonies, Paraphrases, and Gospel Interpretation -- 3. Freethinkers and Deists -- 4. Periodization and Book Culture -- 5. Conclusions -- Chapter 3 -- The Galilean Crisis in the Nineteenth-Century Quest -- 1. Reimarus and Stratification -- 2. Hase in Proper Historical Context -- 3. The Crisis Theory in Later Lives of Jesus -- 4. Assessing the Nineteenth-century Crisis Theory -- 5. Conclusions -- Chapter 4 -- The Afterlife of the Crisis Theory -- 1. The Impact of Wrede and Form Criticism -- 2. A Galilean Crisis After Form Criticism -- 3. The Crisis Theory and the "Q People" -- 4. Assessing the Twentieth- to Twenty-first-century Crisis Theory -- 5. Conclusions -- Chapter 5 -- Consistency and Change -- 1. Possibilities -- 2. Early Perceptions of Jesus -- 3. Jesus and John the Baptist -- 4. Jesus and the Scriptures -- 5. Conclusions -- Chapter 6 -- Development: Early Success and Growing Opposition -- 1. A "Galilean Spring"? -- 2. Jesus and the Law: Initial Suggestions -- 3. Identifying "Development" in Retrospect -- 4. Conclusions -- Chapter 7 -- The Rejection of Jesus -- 1. The Galilean Woes -- 2. Theologizing Rejection -- 3. Conclusions -- Chapter 8 -- Final Thoughts -- Bibliography -- Index of Biblical Writings -- Author Index -- Subject Index